G-quadruplex ligands targeting telomeres do not inhibit HIV promoter activity and cooperate with latency reversing agents in killing latently infected cells. Issue 18 (16th September 2020) - Piekna-Przybylska, Dorota; Bambara, Robert A.; Maggirwar, Sanjay B.; Dewhurst, Stephen
ABSTRACT: Altered telomere maintenance mechanism (TMM) is linked to increased DNA damage at telomeres and telomere uncapping. We previously showed that HIV-1 latent cells have altered TMM and are susceptible to ligands that target G-quadruplexes (G4) at telomeres. Susceptibility of latent cells to telomere targeting could potentially be used to support approaches to eradicate HIV reservoirs. However, G4 ligands also target G-quadruplexes in promoters blocking gene transcription. Since HIV promoter sequence can form G-quadruplexes, we investigated whether G4 ligands interfere with HIV-1 promoter activity and virus reactivation from latency, and whether telomere targeting could be combined with latency reversing agents (LRAs) to promote elimination of HIV reservoirs. Our results indicate that Sp1 binding region in HIV-1 promoter can adopt G4 structures in duplex DNA, and that in vitro binding of Sp1 to G-quadruplex is blocked by G4 ligand, suggesting that agents targeting telomeres interfere with virus reactivation. However, our studies show that G4 agents do not affect HIV-1 promoter activity in cell culture, and do not interfere with latency reversal. Importantly, primary memory CD4 + T cells infected with latent HIV-1 are more susceptible to combined treatment with LRAs and G4 ligands, indicating that drugs targeting TMM may enhance killing of HIV reservoirs. Using a cell-based DNA repair assay, we also found that HIV-1 infected cells have reduced efficiency of DNA mismatch repair (MMR), and base excision repair (BER), suggesting that altered TMM in latently infected cells could be associated with accumulation of DNA damage at telomeres and changes in telomeric caps.